EFEKTIFITAS PENGGUNAAN STRATEGI PEMBELAJARAN REACT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI MACROMEDIA FLASH DI SMA NEGERI 3 PANYABUNGAN - Nurma Sodikoh (JURNAL MathEdu (Mathematic Education Journal), 2018)
This study aims to describe the effectiveness of using REACT (Relating Experiencing Applying Cooperating Transferring) learning strategy on students’ mathematical problem solving ability on the topic logic through Flash Macro Media at the tenth grade students of SMA Negeri 3 Panyabungan. The research was conducted by using quasi experimental method (pretest post test one group design) with 27 students as the sample and they were taken by using cluster sampling technique from 116 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using REACT learning strategy through Flash Macro Media was 3.73 (very good category) and b) the average of students’ logic achievement before using REACT learning strategy through Flash Macro Media was 53.48 (fair category) and after using REACT learning strategy through Flash Macro Media was 82.81 (very good category).Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant influence of using REACT learning strategy on students’ mathematical problem solving ability on the topic logic through Flash Macro Media.